Pemanfaatan Lingkungan Sekitar Sebagai Sumber Belajar Mata Pelajaran IPS di SD Negeri Unggulan Bontomanai Kecamatan Bontomarannu Kabupaten Gowa - Andi Dian Yusran; Patahuddin Patahuddin; Maharuddin Pangewa; Muhamad Ihsan Azhim (Phinisi Integration Review, 2022)
The study aims to examine and describe the social studies learning process by utilizing the surroundings of environment as a learning resource at SDN Unggulan (Distinguished Public Elementary School) Bontomanai in Bontomarannu subdistrict in Gowa district, the effectiveness of social studies learning by utilizing the surroundings as a learning resource at SDN Uggulan Bontomanai in Bontomarannu subdistrict in Gowa district, and the supporting and inhibiting factors in social studies learning by utilizing the surroundings as a learning resource at SDN Uggulan Bontomanai in Bontomarannu subdistrict in Gowa district. This type of the study employed descriptive qualitative research by determining the number of informants consisting of 8 informants selected by purposive sampling technique with the criteria of informants were the principals, teachers, parents, and students at SDN Unggulan Bontomanai. The data collection techniques employed observation, interviews, and documentation. The data analysis techniques used by the researcher were conducted in three work stages, namely data reduction, data presentation, and conclusion drawing. The data validation techniques used were source triangulation and method triangulation. The results of the study reveal that (1) the social studies learning by utilizing the surroundings as a learning resource at SDN Uggulan Bontomanai in Bontomarannu subdistrict in Gowa district is in three stages including the planning stage, the implementation stage, and the evaluation stage in the learning process by using the surroundings as a learning resource, (2) the effectiveness of social studies learning by utilizing the surroundings as a learning resource at SDN Uggulan Bontomanai in Bontomarannu subdistrict in Gowa district had been conducted well and smoothly in every learning process conducted, and (3) the supporting and inhibiting factors in social studies learning by utilizing the surroundings as a learning resource at SDN Uggulan Bontomanai in Bontomarannu subdistrict in Gowa district are the availability of spacious land, the availability of supporting facilities and infrastructure for learning in outdoor, and the availability of equipment needed in an effort to utilize the school surroundings as a learning media; whereas, the inhibiting factor was not a factor that prevented teachers from utilizing the natural environment as a learning media, but instead as a challenge for teachers at SD Negeri Bontomanai.